An Exploration of Key Phrase Frames in Business Management Discussions for EAP Teaching - He, Mengyu; ANG, Leng Hong; Abdul Rahim, Hajar (Círculo de Lingüística Aplicada a la Comunicación, 2024)
The interest in the phraseological nature of language generated many studies on phraseology in different genres. The focus of the current study is on key phrase frames in business management research article discussions. Key phrase frames are recurrent phraseological expressions with a variable slot and are specific to the studied context, for example genre or discipline. The analysis of the study is based on a corpus of research article discussions, extracted from six leading journals in business management, published between 2017 and 2021. Four-word phrase frames in the corpus were searched using the KfNgram program and refined based on the exclusion criteria to generate a list of phrase frames that was compared with the Corpus of Contemporary American English.The comparison yielded a total of 63 four-word key phrase frames in business management that were analyzed following Biber and Gray's (2013) structural classification and Simpson-Vlach and Ellis's (2010) functional taxonomy. In terms of structure, most key phrase frames were found to be non-verb content word frames while functionally, most serve referential discourse functions. The results suggest that phraseological variation in business management is associated with both lexical and grammatical constructions. These findings are crucial as they have implications on discipline-specific academic writing. most key phrase frames were found to be non-verb content word frames while functionally, most serve referential discourse functions.The results suggest that phraseological variation in business management is associated with both lexical and grammatical constructions. These findings are crucial as they have implications on discipline-specific academic writing. most key phrase frames were found to be non-verb content word frames while functionally, most serve referential discourse functions. The results suggest that phraseological variation in business management is associated with both lexical and grammatical constructions. These findings are crucial as they have implications on discipline-specific academic writing.
Keywords: phraseology; research article; key phrase frame; discipline-specific writing